New High-Performance Fluorescent Dye Scaffolds: Applications for Bioimaging and Biosensing - Cheng, Junfeng; Lei, Zuhai (Synlett, 2023)
Fluorescence imaging in the shortwave infrared region (SWIR, 850–2500 nm) window has become an indispensable tool in biomedical research because it has weaker absorption, less light scattering, and less background fluorescence in this window. As we know, the design and synthesis of fluorescent dyes and fluorescent probes are the cores of fluorescence imaging and biosensing. Thus, their photophysical mechanisms exploring and bioanalytical applications are multidisciplinary and cutting-edge research topics. In this regard, we have been working on high-performance fluorescent dyes and fluorescent probes for years. In short, we have developed a series of bright, stable, aggregation-resistant, SWIR fluorescent dyes ECXs, based on a carbon-bridged spiro ring strategy. We also developed a series of high-performance SWIR fluorescent dyes CXs and Chrodols, which combine the structural advantages of cyanine and xanthenoid dyes. Based on these new SWIR scaffolds, we further constructed some activatable SWIR fluorescent probes with OFF-ON or ratiometric properties for biosensing in vivo. Therefore, the main line of our work is to gain an in-depth understanding of the photophysical mechanisms of fluorescent dyes, to create high-performance luminescent dyes, and to further develop fluorescent probes for bioimaging and biosensing.1 Introduction2 ECX Dyes Based on a Carbon-Bridged Spiro Ring Strategy3 Fluorescent Dyes and Fluorescent probes Combining the Structures of Cyanine and Xanthenoid Dyes3.1 CX Series Dyes3.2 A Functionalized Modified CX probe NRh3.3 CX-like Dyes with a Secondary Amino Py-23.4 Chrodol Series Dyes4 Conclusion and Future Prospects
Keywords: fluorescence imaging; short-wave infrared; new scaffolds; fluorescent dyes; fluorescent probes